Novel spirooxindole-triazole derivatives: unveiling [3+2] cycloaddition reactivity through molecular electron density theory and investigating their potential cytotoxicity against HepG2 and MDA-MB-231 cell lines - Shawish, Ihab; Al Ayoubi, Samha; El-Faham, Ayman; Aldalbahi, Ali; El-Senduny, Fardous F.; Badria, Farid A.; Ríos-Gutiérrez, Mar; Hammud, Hassan H.; Ashraf, Sajda; Ul-Haq, Zaheer; Barakat, Assem (Frontiers in Chemistry, 2024)
A novel analogue of hybrid spirooxindoles was synthesized employing a systematic multistep synthetic approach. The synthetic protocol was designed to obtain a series of spirooxindole derivatives incorporating triazolyl-s-triazine framework via [3+2] cycloaddition (32CA) reaction of azomethine ylide (AY) with the corresponding chalcones (6a-d). Unexpectedly, the reaction underwent an alternate route, leading to the cleavage of the s-triazine moiety and yielding a series of spirooxindole derivatives incorporating a triazole motif. A comprehensive investigation of the 32CA reaction mechanism was conducted using the Molecular Electron Density Theory (MEDT). The viability of all compounds was evaluated through an MTT assay, and the IC50 values were determined using Prism Software. The antiproliferative efficacy of the synthesized chalcones and the corresponding spirooxindole derivatives was assessed against two cancer cell lines: MDA-MB-231 (late-stage breast cancer) and HepG2 (human hepatoma). These findings were compared with Sorafenib, which was used as a positive control. The results revealed that chalcones (6c and 6d) were the most active among the tested chalcones, with IC50 values of 7.2 ± 0.56 and 7.5 ± 0.281 µM for (6c) and of 11.1 ± 0.37 and 11.0 ± 0.282 µM for (6d), against MDA-MB-231 and HepG2, respectively. Spirooxindoles (9b, 9c, 9h, and 9i) exhibited the highest activity with IC50 values in the range ranging from 16.8 ± 0.37 µM to 31.3 ± 0.86 µM against MDA-MB-231 and 13.5 ± 0.92 µM to 24.2 ± 0.21 µM against HepG2. Particularly, In particular, spirooxindole derivatives incorporating 2,4dichlorophenyl moiety were the most active, with an IC50 of µM of 16.8 ± 0.37 µM for (9h) against MDA-MB-23 and 13.5 ± 0.92 µM for (9i) against HepG2. Interestingly, the IC50 of compound 6c (7.2 µM) exhibited better activity than that of Sorafenib (positive control) (9.98 µM) against MDA-MB-231. Molecular docking, ADMET, and molecular dynamic simulation explored for the promising candidates 6b, 6c, and 9h for binding affinity in the EGFR active site. Molecular docking, ADMET, and molecular dynamic simulations were conducted for the promising candidates (6b, 6c, and 9h) to explore their binding affinity in the EGFR active site.